Design of a Modern Car Parking at the Faculty of Engineering, Technology Aplied Design and Fine Art. - Barusya, Grant (Kabale University, 2023)
This report contains several chapters giving an overview of the activities we carried out during the design of modern car parking at Nyabikoni campus. The activities include the following, Drawing plan, Demarcating the parking model using the molding board Dimensioning the model using arch card 2017 and auto card 2020 Cutting the plywood, Fixing grasses and trees using super glue.